2021
DOI: 10.1017/s1471068421000211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Transformation of Constrained Horn Clauses for Program Verification

Abstract: This paper surveys recent work on applying analysis and transformation techniques that originate in the field of constraint logic programming (CLP) to the problem of verifying software systems. We present specialization-based techniques for translating verification problems for different programming languages, and in general software systems, into satisfiability problems for constrained Horn clauses (CHCs), a term that has become popular in the verification field to refer to CLP programs. Then, we describe sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 236 publications
0
9
0
Order By: Relevance
“…The CHC translation of a contract verification problem for a functional or an imperative program (Grebenshchikov et al 2012;De Angelis et al 2021) produces three sets of clauses, as shown in Figure 1, where we refer to a program that reverses a list of integers (we omit the source functional program for lack of space). The first set (clauses [1][2][3][4] is the translation of the operational semantics of the program.…”
Section: A Motivating Examplementioning
confidence: 99%
See 2 more Smart Citations
“…The CHC translation of a contract verification problem for a functional or an imperative program (Grebenshchikov et al 2012;De Angelis et al 2021) produces three sets of clauses, as shown in Figure 1, where we refer to a program that reverses a list of integers (we omit the source functional program for lack of space). The first set (clauses [1][2][3][4] is the translation of the operational semantics of the program.…”
Section: A Motivating Examplementioning
confidence: 99%
“…The use of CHCs for program verification has become very popular and many techniques and tools for translating program verification problems into satisfiability problems for CHCs have been proposed (see, for instance, the surveys by Bjørner et al 2015 andby De Angelis et al 2021). However, as also shown in this paper, in the case of clauses with ADT terms, state-of-the-art CHC solvers have some severe limitations due to the fact that they do not include any proof technique for inductive reasoning on the ADT structures.…”
Section: Related Work and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHC translation of a contract verification problem for a functional or an imperative program (Grebenshchikov et al 2012;De Angelis et al 2021) produces three sets of clauses, as shown in Figure 1, where we refer to a program that reverses a list of integers (we omit the source functional program for lack of space). The first set (clauses 1-4) is the translation of the operational semantics of the program.…”
Section: A Motivating Examplementioning
confidence: 99%
“…The front end is also in charge of these translations, as well as of translating the analysis and verification results back to the source language. Techniques such as partial evaluation and program specialization offer powerful methods to obtain such translations with provable correctness-see(De Angelis et al 2021) for a recent survey. 2 https://github.com/ciao-lang/devenv…”
mentioning
confidence: 99%